Cancel culture and boycotting : Why consumers participate in boycotting commercial entities in Finland, Germany, and the United States - Tornberg, Sarah (2024)
This thesis aims to describe how cancel culture and related boycotting tendencies might affect commercial entities, such as brands and businesses. First, earlier research and the descriptive level of cancel culture and boycotting are described. The possible consequences of cancel culture on brands and businesses are explored, and how commercial entities have adapted to the era of cancel culture. The research data is analyzed to determine why survey respondents have previously boycotted someone, as well as whom they have boycotted. The data gathered from university students in Finland (n=225), Germany (n=221), and the United States (n=173) is analyzed using exploratory factor analysis, two-way analysis of variance, and multiple linear regression to find similarities, differences, and boycotting tendencies by comparing the countries’ results. Four boycotting factors describes the reasons for boycotting: ethical boycotting, quality boycotting, value boycotting, and nationality boycotting, while brands, social media influencers and organizations are the most boycotted entities. The analysis supports earlier research; young women are the most prominent boycotters, although men were the most active boycotters due to nationality in each of the three countries. Country of residence, gender and age were not the strongest predictors of the respondents’ boycott practices indicating that some other reasons would better explain participating in consumer boycotts.